Bedaya Duradasih, Sebuah Ekspresi Budaya pada Masa Sunan Pakubuwana III-IV di Keraton Surakarta - Indah Nuraini; Supriyanti Supriyanti (Dance and Theatre Review, 2021)
Bedaya Duradasih: A Cultural Expression During the time of Sunan Pakubuwana III-IV in the Surakarta Palace. Bedaya Duradasih is a form of bedaya dance created at the Surakarta Palace. Its creator was Sunan Pakubuwana IV who at that time, still had the title of Kanjeng Gusti Pangeran Adipati Anom. Sunan Pakubuwana IV was a king who had a very significant artistic spirit, so it cannot be denied that artistic and cultural life was very flourishing during his reign. Bedaya Duradasih was one of the cultural expressions at that time. The created expression was inspired by the mood of being infatuated/falling in love with the Madurese princess. Looking at the words Duradasih and Madura can be connected with several opinions regarding the meaning of the word Duradasih. It is said that Duradasih derived from the words Dura and dasih, which mean a woman from Madura. Then it is also mentioned from the words Dara and dasih, which means girl/virgin who brings happiness. Furthermore, it is interpreted from the words Dora and dasih, which means lying for political interests at that time, which ended up with a love affair. From these descriptions, it can be concluded that Bedaya Duradasih reflects one of the cultural expressions.Keywords: bedaya; Surakarta; expression